Battery temperature monitoring system using Arduino - Srujana, Boddireddy; Chenchireddy, Kalagotla; Sujatha, Muthumula; Sultana, Waseem; Ahmed Sydu, Shabbier; Giddalur, Eswaraiah (International Journal of Advances in Applied Sciences, 2025)
Energy storage technologies are playing a key role in the modern world. The energy storage technologies are battery and ultracapacitors. This paper presents designing and implementing an Arduino-based battery temperature monitoring system for real-time battery temperature monitoring in a variety of applications, including industrial equipment, renewable energy systems, and electric cars. An Arduino microcontroller, temperature sensors, and optional display and communication modules make up the system. The Arduino receives temperature data from the sensors and processes it to provide information, send out alerts, and log data for further analysis. The technology provides an affordable and adaptable way to guarantee both the safety and best possible performance from batteries.